PERAN SENI TEATER DALAM MENTRANSFER NILAI-NILAI AKHLAK PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM - Fajar, Fajar; Ridhwan, Ridhwan (JURNAL AL-QAYYIMAH, 2021)
This paper examines the role of theater arts in transferring moral values in islamic cultural history learning. This paper aims to reveal the meaning and origin of theater as well as the moral values contained in learning the history of Islamic culture through theater. The research method uses literature review. The results of the research show that theater is a matter of mysticism, in my eyes there are many things that can be tried in theater, because the crisis experienced by the Indonesian state for me is a spiritual tension. At first the theater was only performed for ritual purposes only about thousands of years BC. From several ancient nations that experienced rapid cultural development such as Ancient Egypt, Maya in South America, Central Asia, Babylon, China and India, theater was used as a medium that could bring them in direct contact with the Almighty. Along with the development of the times, the Greeks changed the design pattern in developing theatrical performances, not only centered on rituals, but can also be presented as an entertainment spectacle.Theater can be a medium for forming Muslim personalities and can be done through learning the history of Islamic culture. With this method, this formation will be reflected in the moral personality of students, which includes noble moral values which include religious values, discipline, independence, responsibility, creativity, cooperation and care for the environment.